A Perception on Industry Revolution 4.0 Digital Age and Impact on English Learning Motivation to the Students of Islamic Higher Education - Hasanah, Uswatun; Arqam, Arqam (Al-Iftah: Journal of Islamic studies and society, 2021)
This research aimed to investigate a perception on industry revolution 4.0 digital age and its impact on English learning motivation to the students of higher education. This research was carried out two universities at Parepare (Muhammadiyah University and IAIN Parepare) with 87 participants consist of the students of the first semester in the academic year 2019/2020. This study was quantitative research. The instruments of data collection are questionnaires. The researcher used the formula of SPSS computer to analyze and calculate data. The result of the data that the students’ perception on industry revolution 4.0 is positive and the mean score is 40,89%. The students’ motivation in English learning is high and the mean score is 41,38%. Based on the calculation by using SPSS 16 Program, it was found that Rvalue = 0,496 was higher than Rtable = 5% (0,2108) or 1% (0,2748) at df = 85. Therefore, coefficient correlation Rvalue = 0,496 was categorized into moderate correlation. It meant that there was a significant positive correlation between the students’ perception on industry revolution 4.0 and the students’ motivation in English learning.